Ketogenic diets are beneficial for athletic performance - Noakes, T. D. (Medicine & Science in Sports & Exercise, 2024)
An iconic 1967 study proved that a 7-d ketogenic (low-carbohydrate high-fat [LCHF]) diet impairs performance when eaten by athletes habituated to a high-carbohydrate low-fat (HCLF) diet (1).